Nigerian Dress: The Body Honoured: The Custume Arts of Traditional Nigerian Dress from Early History to Independence - Lyndersay, Dani (Centre for Black and African Arts and Civilization, 2011)
This book contains a systematic survey of the dress modes of major Nigerian ethnic groups. The work is based on fieldwork done in Nigeria between the years 1960 and 1988. The study also draw on archaeological findings, figurative sculptures, textiles, extant archival photographs, and facial and body decorative traditions...
Keywords: Costume Arts; Non-Fiction